Clinical And Functional Outcome Between All Arthroscopic Vs. Mini-Open Surgery in Rotator Cuff Injury: A Meta-Analysis - Stedy Adnyana Christian; Shianita Limena (GLOBAL HEALTH SCIENCE GROUP, 2023)
Rotator cuff tear portrays a frustrating experience with shoulder dysfunction and disability. Surgical repair showed satisfactory results when conservative treatment failed or not-indicated. Along with the surgical advancement, mini-open and arthroscopic surgery have a growing preference with minimal scarring, desirable pain relief, and functional improvement. To date, there are inconclusive results on which type of surgery is superior. Functional outcome and complication rates are equally balanced between the two surgeries, while some studies favor arthroscopic repair. The aim of study is to compare the clinical and functional outcome between arthroscopy and mini-open surgery for rotator cuff repair according to recent publications. This study conducted a thorough search for relevant scientific reports on multiple medical databases, including PubMed, Embase, and Google Scholar, using a combination of keywords such as